Effect of chronic alcohol ingestion on the progression of periodontitis induced in Fisher-344 rats - Éder Ricardo Biasoli; Tereza Aparecida Delle Vedove Semenoff; Alex Semenoff Segundo (Faculdade São Leopoldo Mandic, 2009)
Objective: Understand the effect of chronic alcohol on the progression of periodontitis induced in Fischer-344 rats.Methods: For the study, 22 Fischer-344 rats, two months old were used, divided into groups: alcohol (n=8), ligature (n=7) and control (n=7). On the first day, the animals in the alcohol group were exposed to ingestion of a water solution containing 20% alcohol (size/size), up to day 90. After thirty days from the beginning of the experiment, the animals in the alcohol group and the ligature group were submitted to the placement of a silk thread around the right maxillary second molar. Nothing was performed on the left side, serving as control. All the groups were submitted to euthanasia 60 days after ligature placement. To assess the destruction of periodontitis, a radiographic exam was used to measure the destruction of bone height. Results: The results of the study showed that on the side in which periodontitis was induced, the group that ingested alcohol suffered an increase in destruction, with statistical differences when compared with the ligature and control groups and increased bone destruction in the ligature group when compared to control. Conclusion: Within the limitations of the study, it was concluded that chronic alcohol consumption by Fischer-344 rats led to greater progression of induced periodontitis.